Highly sensitive and efficient 1550 nm photodetector for room temperature operation - Rituraj; Zhi Gang Yu; R. M. E. B. Kandegedara; Shanhui Fan; Srini Krishnamurthy (AIP Advances)
Photonic quantum technologies such as effective quantum communication require room temperature (RT) operating single- or few-photon sensors with high external quantum efficiency (EQE) at 1550 nm wavelength. The leading class of devices in this segment is avalanche photodetectors operating particularly in the Geiger mode. However, for superior performance, a trade-off has to be made between temperature of operation, device thickness, and EQE. Two-dimensional (2D) materials can be used to reduce the absorber thickness and thus dark current, leading to an increase in the operating temperature, but they suffer from low EQE. We use specifically stacked bilayer hexagonal BAs, with material properties calculated from first principles, on a co-optimized dielectric photonic crystal substrate to simultaneously decrease the dark current by three orders of magnitude at RT and maintain an EQE of >99%. The device can potentially be used in avalanche mode and hence can form a basis for single photon detection.